2021
DOI: 10.3389/fphys.2021.637924
|View full text |Cite
|
Sign up to set email alerts
|

A Subpopulation of Schwann Cell-Like Cells With Nerve Regeneration Signatures Is Identified Through Single-Cell RNA Sequencing

Abstract: Schwann cell-like cells (SCLCs) derived from human amniotic mesenchymal stem cells (hAMSCs) have been shown to promote peripheral nerve regeneration, but the underlying molecular mechanism was still poorly understood. In order to investigate the heterogeneity and potential molecular mechanism of SCLCs in the treatment of peripheral nerve regeneration at a single cell level, single-cell RNA sequencing was applied to profile single cell populations of hAMSCs and SCLCs. We profiled 6,008 and 5,140 single cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The data clustered into 10 cell groups and were defined based on characteristic genes in previously published single cell data for each particular cell type (Fig. 2C) [32][33][34][35][36][37][38][39][40][41] . -Cell counts were obtained from the single nuclei RNA seq analysis and each cluster's percentage was reported (Fig.…”
Section: Reparative Peripheral Nerve Tissue Contains Transcriptionall...mentioning
confidence: 99%
“…The data clustered into 10 cell groups and were defined based on characteristic genes in previously published single cell data for each particular cell type (Fig. 2C) [32][33][34][35][36][37][38][39][40][41] . -Cell counts were obtained from the single nuclei RNA seq analysis and each cluster's percentage was reported (Fig.…”
Section: Reparative Peripheral Nerve Tissue Contains Transcriptionall...mentioning
confidence: 99%
“…Single cell RNA-seq (scRNA-seq) data from human amniotic mesenchymal stem cells (hAMSCs) differentiated to Schwann like cells (SLCs) was downloaded from Gene Expression Omnibus (GSE161066) [29]. The Seurat R package [34] was used for initial data cleaning and quality control, removing cells with < than 200 or > 2,500 unique feature counts as well as cells with > 5 percent mitochondrial RNAs.…”
Section: Methodsmentioning
confidence: 99%
“…We further refine the putative roles of these modules using functional enrichment analysis [28]. To validate our findings, we compared the DEGs and gene modules derived from our hiPSC induced Schwann cells with two independent single cell and bulk transcriptomic datasets of human Schwann cell differentiation [29] and mouse sciatic nerve development [30].…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] According to expression of differential genes, the subgroups of malignant cells were annotated as follows: (1) the MES-like malignant cells with high expression of VIM; (2) the OPC-like malignant cells characterized with high OLIG1, ALCAM and PLP1 expression; (3) the NPC-like malignant cells highly expressing SOX4, SOX11 and DCX; (4) the malignant cells related to proliferation expressing the proliferation markers MKI67, CENPF, TOP2A (Figure 3B-D). 42,44,45 We found that markers of AC-like cells (GFAP, S100B, SLC1A3) were widely expressed in each subgroup, so none of the subgroups was annotated as AC-like malignant cells (Figure 3C,D). 42 Interestingly, we noticed that another mesenchymal marker CD44 was highly expressed only in clusters 0 and 4 but not in cluster 6 (Figure 3C,D).…”
Section: Landscape Of Malignant Cells In the Immune Microenvironment ...mentioning
confidence: 99%